Co-inoculation of protist and Bacillus enhances plant growth via reshaping rhizosphere bacterial community composition and function - Qihui LÜ; Chen LIU; Ying GUI; Yang YUE; Xiao WANG; Zeyuan ZHOU; Ying YUAN; Yijing WANG; Boting XU; Zhihui XU; Mohammadhossein RAVANBAKHSH; Alexandre JOUSSET; et al. (Pedosphere, 2025)

Exploring the antibiotic resistance genes removal dynamics in chicken manure by composting - Yaozhong Zhang; Ningqi Wang; Jinxing Wan; Alexandre Jousset; Gaofei Jiang; Xiaofang Wang; Zhong Wei; Yangchun Xu; Qirong Shen (Bioresource Technology, 2024)

Protist communities as indicators of fertilization-induced changes in a species-rich grassland ecosystem - Shuo Sun; Alexandre Jousset; Stefan Geisen; Enrique Lara; Pengfei Zhang; Rong Li; Francisco Dini-Andreote; Mohammadhossein Ravanbakhsh; Qirong Shen; George A. Kowalchuk; Wu Xiong (Agriculture, Ecosystems & Environment, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Intercropping with Trifolium repens contributes disease suppression of banana Fusarium wilt by reshaping soil protistan communities - Xiangyu Ren; Zeyuan Zhou; Manyi Liu; Zongzhuan Shen; Beibei Wang; Alexandre Jousset; Stefan Geisen; Mohammadhossein Ravanbakhsh; George A. Kowalchuk; Rong Li; Qirong Shen; Wu Xiong (Agriculture, Ecosystems & Environment, 2024)

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

RIN enhances plant disease resistance via root exudate-mediated assembly of disease-suppressive rhizosphere microbiota - Keming Yang; Ruixin Fu; Haichao Feng; Gaofei Jiang; Omri Finkel; Tianyu Sun; Mingchun Liu; Baowen Huang; Shan Li; Xiaofang Wang; Tianjie Yang; Yikui Wang; et al. (Molecular Plant, 2023)

Coming of age for the rhizosphere microbiome transplantation - Alexandre Jousset; Seon-Woo Lee (Soil Ecology Letters, 2023)

Resource availability drives bacteria community resistance to pathogen invasion via altering bacterial pairwise interactions - Mei Li; Thomas Pommier; Yue Yin; Wenhui Cao; Xiaohui Zhang; Jie Hu; Yann Hautier; Tianjie Yang; Yangchun Xu; Qirong Shen; George A. Kowalchuk; Alexandre Jousset; et al. (Environmental Microbiology, 2022)
Microbial interactions within resident communities are a major determinant of resistance to pathogen invasion. Yet, interactions vary with environmental conditions, raising the question of how community composition and environments interactively shape invasion resistance. Here, we use resource availability (RA) as a model parameter altering the resistance of model bacterial communities to invasion by the plant pathogenic bacterium Ralstonia solanacearum . We found that at high RA, interactions between resident bacterial species were mainly driven by the direct antagonism, in terms of the means of invader inhibition. Consequently, the competitive resident communities with a higher production of antibacterial were invaded to a lesser degree than facilitative communities. At low RA, bacteria produced little direct antagonist potential, but facilitative communities reached a relatively higher community productivity, which showed higher resistance to pathogen invasion than competitive communities with lower productivities. This framework may lay the basis to understand complex microbial interactions and biological invasion as modulated by the dynamic changes of environmental resource availability.

Effect of mutation supply on population dynamics and trait evolution in an experimental microbial community - Johannes Cairns; Alexandre Jousset; Lutz Becks; Teppo Hiltunen (Ecology Letters, 2022)
Mutation supply can influence evolutionary and thereby ecological dynamics in important ways which have received little attention. Mutation supply influences features of population genetics, such as the pool of adaptive mutations, evolutionary pathways and importance of processes, such as clonal interference. The resultant trait evolutionary dynamics, in turn, can alter population size and species interactions. However, controlled experiments testing for the importance of mutation supply on rapid adaptation and thereby population and community dynamics have primarily been restricted to the first of these aspects. To close this knowledge gap, we performed a serial passage experiment with wild‐type Pseudomonas fluorescens and a mutant with reduced mutation rate. Bacteria were grown at two resource levels in combination with the presence of a ciliate predator. A higher mutation supply enabled faster adaptation to the low‐resource environment and anti‐predatory defence. This was associated with higher population size at the ecological level and better access to high‐recurrence mutational targets at the genomic level with higher mutation supply. In contrast, mutation rate did not affect growth under high‐resource level. Our results demonstrate that intrinsic mutation rate influences population dynamics and trait evolution particularly when population size is constrained by extrinsic conditions.

Rhizosphere microbiome functional diversity and pathogen invasion resistance build up during plant development - Jie Hu; Zhong Wei; George A. Kowalchuk; Yangchun Xu; Qirong Shen; Alexandre Jousset (Environmental Microbiology, 2020)
Summary The rhizosphere microbiome is essential for plant growth and health, and numerous studies have attempted to link microbiome functionality to species and trait composition. However, to date little is known about the actual ecological processes shaping community composition, complicating attempts to steer microbiome functionality. Here, we assess the development of microbial life history and community‐level species interaction patterns that emerge during plant development. We use microbial phenotyping to experimentally test the development of niche complementarity and life history traits linked to microbiome performance. We show that the rhizosphere microbiome assembles from pioneer assemblages of species with random resource overlap into high‐density, functionally complementary climax communities at later stages. During plant growth, fast‐growing species were further replaced by antagonistic and stress‐tolerant ones. Using synthetic consortia isolated from different plant growth stages, we demonstrate that the high functional diversity of ‘climax’ microbiomes leads to a better resistance to bacterial pathogen invasion. By demonstrating that different life‐history strategies prevail at different plant growth stages and that community‐level processes may supersede the importance of single species, we provide a new toolbox to understand microbiome assembly and steer its functionality at a community level.

Facilitation promotes invasions in plant‐associated microbial communities - Mei Li; Zhong Wei; Jianing Wang; Alexandre Jousset; Ville‐Petri Friman; Yangchun Xu; Qirong Shen; Thomas Pommier (Ecology Letters, 2019)
While several studies have established a positive correlation between community diversity and invasion resistance, it is less clear how species interactions within resident communities shape this process. Here, we experimentally tested how antagonistic and facilitative pairwise interactions within resident model microbial communities predict invasion by the plant–pathogenic bacterium Ralstonia solanacearum . We found that facilitative resident community interactions promoted and antagonistic interactions suppressed invasions both in the lab and in the tomato plant rhizosphere. Crucially, pairwise interactions reliably explained observed invasion outcomes also in multispecies communities, and mechanistically, this was linked to direct inhibition of the invader by antagonistic communities (antibiosis), and to a lesser degree by resource competition between members of the resident community and the invader. Together, our findings suggest that the type and strength of pairwise interactions can reliably predict the outcome of invasions in more complex multispecies communities.

Resource availability modulates biodiversity‐invasion relationships by altering competitive interactions - Tianjie Yang; Zhong Wei; Ville‐Petri Friman; Yangchun Xu; Qirong Shen; George A. Kowalchuk; Alexandre Jousset (Environmental Microbiology, 2017)
Summary Community diversity affects the survival of newly introduced species via resource competition. Competitive interactions can be modulated by resource availability and we hypothesized that this may alter biodiversity‐invasion relationships. To study this, we assessed the growth of a bacterial invader, Ralstonia solanacearum , when introduced into communities comprised of one to five closely related resident species under different resource concentrations. The invader growth was then examined as a function of resident community richness, species composition and resource availability. We found that the relative density of the invader was reduced by increasing resident community richness and resource availability. Mechanistically, this could be explained by changes in the competitive interactions between the resident species and the invader along the resource availability gradient. At low resource availability, resident species with a high catabolic similarity with the invader efficiently reduced the invader relative density, while at high resource availability, fast‐growing resident species became more important for the invader suppression. These results indicate that the relative importance of different resident community species can change dynamically along to resource availability gradient. Diverse communities could be thus more robust to invasions by providing a set of significant species that can take suppressive roles across different environments.

Application of biochar reduces Ralstonia solanacearum infection via effects on pathogen chemotaxis, swarming motility, and root exudate adsorption - Yian Gu; Yugang Hou; Dapeng Huang; Zhexia Hao; Xiaofang Wang; Zhong Wei; Alexandre Jousset; Shiyong Tan; Dabing Xu; Qirong Shen; Yangchun Xu; Ville-Petri Friman (Plant and Soil, 2017)

Protozoa stimulate the plant beneficial activity of rhizospheric pseudomonads - Simone Weidner; Ellen Latz; Betina Agaras; Claudio Valverde; Alexandre Jousset (Plant and Soil, 2017)

Pathogen invasion indirectly changes the composition of soil microbiome via shifts in root exudation profile - Yian Gu; Zhong Wei; Xueqi Wang; Ville-Petri Friman; Jianfeng Huang; Xiaofang Wang; Xinlan Mei; Yangchun Xu; Qirong Shen; Alexandre Jousset (Biology and Fertility of Soils, 2016)

Coprophilic amoebae and flagellates, including Guttulinopsis, Rosculus and Helkesimastix, characterise a divergent and diverse rhizarian radiation and contribute to a large diversity of faecal‐associated protists - David Bass; Jeffrey D. Silberman; Matthew W. Brown; Rebecca A. Pearce; Alexander K. Tice; Alexandre Jousset; Stefan Geisen; Hanna Hartikainen (Environmental Microbiology, 2016)
Summary A wide diversity of organisms utilize faecal habitats as a rich nutrient source or a mechanism to traverse through animal hosts. We sequenced the 18S rRNA genes of the coprophilic, fruiting body‐forming amoeba Guttulinopsis vulgaris and its non‐fruiting relatives Rosculus ‘ithacus’ CCAP 1571/3, R. terrestris n. sp. and R. elongata n. sp. and demonstrate that they are related to the coprophilic flagellate Helkesimastix in a strongly supported, but highly divergent 18S sister clade. PCR primers specific to both clades were used to generate 18S amplicons from a range of environmental and faecal DNA samples. Phylogenetic analysis of the cloned sequences demonstrated a high diversity of uncharacterised sequence types within this clade, likely representing previously described members of the genera Guttulinopsis , Rosculus and Helkesimastix , as well as so‐far unobserved organisms. Further, an Illumina MiSeq sequenced set of 18S V4‐region amplicons generated from faecal DNAs using universal eukaryote primers showed that core‐cercozoan assemblages in faecal samples are as diverse as those found in more conventionally examined habitats. These results reveal many novel lineages, some of which appear to occur preferentially in faecal material, in particular cercomonads and glissomonads. More broadly, we show that faecal habitats are likely untapped reservoirs of microbial eukaryotic diversity.

Biodiversity and species identity shape the antifungal activity of bacterial communities - Alexandre Jousset; Joachim Becker; Subhankar Chatterjee; Petr Karlovsky; Stefan Scheu; Nico Eisenhauer (Ecology, 2014)
Soils host diverse communities of interacting microbes and the nature of interspecific interactions is increasingly recognized to affect ecosystem‐level processes. Antagonistic interactions between bacteria and fungi are of particular relevance for soil functioning. A number of soil bacteria produce secondary metabolites that inhibit eukaryotic growth. Antibiosis may be stimulated in the presence of competing bacteria, and we tested if biodiversity within bacterial communities affects their antagonistic activity against fungi and fungal‐like species. We set up Pseudomonas communities of increasing diversity and measured the production of the broad spectrum antifungal compound 2,4‐DAPG and their antagonistic activity against different eukaryotes. Diversity increased DAPG concentration and antifungal activity, an effect due to a combination of identity and interactions between species. Our results indicate that investment of pseudomonads into broad spectrum anti‐eukaryotic traits is determined by both community composition and diversity and this provides new avenues to understand interactions between bacterial and fungal communities.

Ecological and evolutive implications of bacterial defences against predators - Alexandre Jousset (Environmental Microbiology, 2012)
Summary Bacterial communities are often heavily consumed by microfaunal predators, such as protozoa and nematodes. Predation is an important cause of mortality and determines the structure and activity of microbial communities in both terrestrial and aquatic ecosystems, and bacteria evolved various defence mechanisms helping them to resist predation. In this review, I summarize known antipredator defence strategies and their regulation, and explore their importance for bacterial fitness in various environmental conditions, and their implications for bacterial evolution and diversification under predation pressure. I discuss how defence mechanisms affect competition and cooperation within bacterial communities. Finally I present some implications of bacterial defence mechanisms for ecosystem services provided by microbial communities, such as nutrient cycling, virulence and the biological control of plant diseases.

Increasing antagonistic interactions cause bacterial communities to collapse at high diversity - Joachim Becker; Nico Eisenhauer; Stefan Scheu; Alexandre Jousset (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 468–474 Abstract Biodiversity is a major determinant of ecosystem functioning. Species‐rich communities often use resources more efficiently thereby improving community performance. However, high competition within diverse communities may also reduce community functioning. We manipulated the genotypic diversity of Pseudomonas fluorescens communities, a plant mutualistic species inhibiting pathogens. We measured antagonistic interactions in vitro, and related these interactions to bacterial community productivity (root colonisation) and ecosystem service (host plant protection). Antagonistic interactions increased disproportionally with species richness. Mutual poisoning between competitors lead to a ‘negative complementarity effect’, causing a decrease in bacterial density by up to 98% in diverse communities and a complete loss of plant protection. The results emphasize that antagonistic interactions may determine community functioning and cause negative biodiversity–ecosystem functioning relationships. Interference competition may thus be an additional key for predicting the dynamics and performance of natural assemblages and needs to be implemented in future biodiversity models.